Knowledge, Attitude, and Supervision Correlation Analysis in Improving Work Safety Using The Pearson Method at A Tin Ore Refining Company in The Jelitik Industrial Area of Bangka Regency - Ivana Ardhia Larasati; Rika Ernawati; Shofa Rijalul Haq; Nurkhamim Nurkhamim; Tedy Agung Cahyadi (Publikasi Indonesia, 2024)
Occupational safety is a crucial aspect, especially in the mining sector, which has a high risk of accidents due to various factors. These factors include knowledge, attitude, and supervision. Although PT Pemurnian Oreh Timah in the Jelitik Industrial Estate recorded a few incidents of work accidents that occurred in the last 1 year, the risk of work accidents still exists. This study aims to analyze the level of close relationship between independent variables, namely knowledge and attitude, knowledge and supervision, and attitude with supervision in the Engineering Department of PT Pemurnian Oreh Timah in the Jelitik Industrial Estate, Bangka Regency. Pearson's correlation test method was used to analyze questionnaire data from 68 workers in the company's engineering department. The results showed that there was a weak relationship (r = 0.311) between knowledge and attitude, as well as a moderate relationship (r = 0.502) between knowledge and supervision. A moderate relationship (r = 0.484) was also found between attitude and supervision. These findings show that these factors are interrelated, where it is hoped that effective supervision can increase workers' knowledge and attitudes towards occupational safety.